A new r-process star with low abundances of r-process elements. Issue 1 (January 2016) - Frebel, A; Yu, Q; Jacobson, H R
Abstract: Metal-poor stars with measurable r-process element abundances provide key clues to the production site(s) of the r-process and how its products are mixed with the surrounding medium. While the number of stars exhibiting strong enhancements of r-process elements has grown over the years, the lower "floor" of r-process enrichment in metal-poor stars has yet to be established, largely in part due to the difficulty in detecting weak neutron-capture element absorption lines in stellar spectra. Here we present detailed abundances of 16 neutron-capture elements for a star exhibiting the lowest level of r-process enrichment yet detected and still following the solar system r-process pattern. Taken into consideration with most of the r- process enriched stars currently in the literature, the range of r-process element enrichment spanned by this sample is at least ∼1.3dex or a factor of more than 20. That the r-process abundance pattern is unchanged while the degree of enrichment varies may suggest that the r- process yields are constant while the gas mass into which they are mixed varies. Given that all stars have similar [Fe/H] values then suggests that only one or few previous stellar generations provided the observed chemical abundances, meaning that perhaps only one r-process event occurred prior to their formation. This would be consistent with a (near) constant r-process yield per event. Obtaining detailed element abundances for stars with mild r-process element enhancements is necessary to better constrain the ubiquity of the r-process pattern, the yields of r-process elements, and the site of its production.